Land remote sensing and global environmental change NASA's earth observing system and the science of ASTER and MODIS - Ramachandran, Bhaskar; Justice, C. O. (Christopher O.).; Abrams, Michael J.; SpringerLink (Online service). (New York Springer, 2011)
Global environmental change remains a constant theme that resonates worldwide. The dynamics of the Earth system fosters complex spatio-temporal variations that highlight the significance of, and the need to monitor the Earth as a unified whole. Accurate, timely, and reliable data are a precursor to analyze and study several aspects of the integrated Earth system. Remote sensing observations have catalyzed several aspects of Earth system science by providing panoptic views and time-series measurements of the study environment in ways nearly impossible to replicate by traditional ground-based methods. NASA?s Earth Observing System's (EOS) primary goal is to study and understand all interacting components of the Earth as a dynamic system. Land Remote Sensing and Global Environmental Change is an edited compendium that specifically focuses on the terrestrial components of change based on the scientific knowledge derived from data produced by two EOS instruments, ASTER and MODIS, which are part of the Terra and Aqua satellite missions. As global environmental change in the Anthropocene age becomes more ubiquitous, the papers presented in this volume demonstrate the value of EOS for studying the Earth's surface. This volume helps articulate the EOS mission as a rich synergistic confluence of science, engineering, and technology, which helps us decipher how our terrestrial systems both contribute and respond to global environmental change. Audience: The primary audience for this book includes Earth and environmental science researchers and professionals, including those who use land remote sensing data.
Prologue -- Acknowledgments -- Part I: The Earth Observing System and the Evolution of ASTER and MODIS -- Part II: ASTER and MODIS: Instrument Design, Radiometry and Geometry -- Part III: ASTER and MODIS: Data Systems -- Part IV: ASTER Science and Applications -- Part V: MODIS Science and Applications -- Part VI: The Future of Land Remote Sensing -- Index.
Electronic reproduction.
Keywords: Earth Observing System (Program).; Advanced Spaceborne Thermal Emission and Reflection Radiometer (Program).; MODIS (Spectroradiometer).; Electronic books